Leadership and Job Satisfaction of Lecturers in Semarang - Qurnia Fitriyatinur (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to investigate the relationship between leadership styles and job satisfaction of lecturers in higher education institutions. Employing a quantitative research approach, data were collected using two scales: a leadership scale and a job satisfaction scale. The research involved 60 respondents selected through accidental sampling. The results reveal a highly significant positive correlation between leadership and job satisfaction of lecturers, indicating that better leadership is associated with higher job satisfaction among lecturers, and vice versa. This is evident from the Spearman's Rho coefficient of 0.173 with a significance level of 0.000 (P < 0.01).